The Transferability Level of Junior High School Students in Solving Geometry Problems - Anisa Agustin; Endah Retnowati; Khar Thoe Ng (Yayasan Keluarga Guru Mandiri, 2022)
Transferability indicates that learners are able to use their knowledge to solve advanced problems. This study aimed to elaborate in detail the level of transferability both near andÂ far transferability of junior high school students in solving geometry problems, and to reveal some factors causing errors in doing the transfer test. Geometry in this study covered solid prism and pyramid. This qualitative descriptive study involved as many as 157 Grade VIII students in one of the junior high schools in Sleman Regency, Indonesia. The data were collected through a written test taken by all participants and interviews with 16 students selected based on the category of the transfer test results. This results of the study showed that (1) based on the average test scores, all students acquired fair transferability, (2) based on the near transfer test item, all students could be categorized as having high transferability, (3) based on the far transfer test items, all students could be categorized as having low transferability, (4) The factors that caused student errors were: (i) difficulties in showing information of what is known in the given context of the transfer problem; (ii) difficulties in stating what is asked in the given problems; (iii) difficulties in using conceptual, procedural, and technical knowledge in executing the strategy of solution; (iv) difficulties in drawing correct conclusions. This result of this study have raised concerns regarding the importance of learning strategy that facilitate transferability.